Novel patient-derived xenograft mouse model for pancreatic acinar cell carcinoma demonstrates single agent activity of oxaliplatin. Issue 1 (December 2016) - Hall, Jason; Marlow, Laura; Mathias, Adam; Dawson, Louis; Durham, William; Meshaw, Kenneth; Mullin, Robert; Synnott, Aidan; Small, Daniel; Krishna, Murli; Hoff, Daniel; Schüler, Julia; et al.
Abstract Background Pancreatic acinar cell carcinoma (PACC) is a rare malignancy, accounting for <1 % of all pancreatic neoplasms. Very few retrospective studies are available to help guide management. We previously reported the case of a patient with metastatic PACC who achieved prolonged survival following doxorubicin treatment. Personalized treatment was based on molecular and in vitro data collected from primary cells developed from their liver metastasis. We now report the characterization of a patient derived tumor xenograft (PDTX) mouse model that originated from this patient's PACC liver metastasis. Methods Fragments of biopsy tissue (5 mm3 ) from PACC liver metastasis were implanted into athymic nude mice. Tumors were grown and passaged from the host mice into new mice to be tested for therapeutic response. Immuno-histochemical (IHC) biomarkers were used to confirm that the PDTX model represents human PACC. The antitumor activities of multiple drugs (5-FU, irinotecan, oxaliplatin, gemcitabine, bevacizumab, erlotinib, doxorubicin and imatinib) were tested. Tumor size was measured over 74 days or until they reached an endpoint volume of ~800 mm3 . Tests to measure serum lipase levels and histological analyses of tumor tissues were also conducted to assess PACC progression and re-differentiation. Results The model presented here expresses the same IHC markers found in human PACC. In the chemotherapy study, oxaliplatin produced a prolonged durable growth response associated with increased apoptosis, decreased serum lipase levels and increased healthy acinar cells. Bevacizumab also produced a significant growth response, but the effect was not prolonged as demonstrated by oxaliplatin treatment. The other chemotherapies had moderate to little effect, particularly after treatment ceased. Mutations in DNA repair genes are common in PACC and increase tumor susceptibility to oxaliplatin. To explore this we performed IHC and found no nuclear expression of BRCA2 in our model, indicating a mutation affecting nuclear localization. Gene sequencing confirms BRCA2 has a homozygous gene deletion on Exon 10, which frequently causes a protein truncation. Conclusions In summary, we report the development and characterization of the first and only preclinical PACC PDTX model. Here we show sustained anti-tumor activity of single agent oxaliplatin, a compound that is more effective in tumors that harbor mutations in DNA repair genes. Our data shows that BRCA2 is mutated in our PACC model, which could contribute to the oxaliplatin sensitivity observed. Further studies on this rare PACC model can serve to elucidate other novel therapies, biomarkers, and molecular mechanisms of signaling and drug resistance.